ANALISIS EKONOMI KOMODITI KELAPA-DALAM (COCOS NUCIFERA L) GUNA MENINGKATKAN KEUNTUNGAN PETANI DI WILAYAH PASANG SURUT PROVINSI JAMBI - Ningsih, Rozaina (Universitas Jambi, 2018)
Jambi Province has several leading plantation commodities which have made a significant contribution, consisting of rubber, palm oil, deep coconut and several other plantation commodities. There are some interesting things that need to be a concern for the development of coconut commodities, the problem can be divided into 3 categories namely the nature of the commodity, the nature of the market mechanism and the geographical nature of its production. First, allegations began to appear as an inferior coconut for households in this region. inferior. Second, the condition where the amount of copra (coconut) production exceeds the amount of demand by the processing industry (QS> QD). Third, from the geographical side of Tanjung Jabung Barat and Tanjung Jabung Timur Regencies, most of them have specific conditions, namely tidal (peat) areas, isolated. The purpose of this study is to examine the pressures from several field conditions, namely: (1). The inferior characteristics of the coconut commodity to farmers' profits. Excess supply of coconut commodities to farmers' profit. (2). Excess supply of coconut commodities to farmers' profit (3). Isolation of the location of a deep-coconut garden to farmers' profit. The results of the analysis show that the production of the coconut commodity is characterized by local characteristics, namely: (a). The coconut-in commodity is inferior (b). Coconut commodity with excess supply (c). Isolation of the location of a deep coconut commodity garden. The distinctive character of the coconut-commodity in each has a negative influence on the benefits received by farmers. Analysis shows that the coconut-in commodity is proven to be inferior, then partially there is a significant influence of the amount of consumption on the profits of farmers. b. The advantage of farmers with easy accessibility is that there is no excess supply (D = 1) higher than the profits of farmers, which occurs excess supply (D = 0). c. There is a significant difference between the profits of coconut farmers whose plantation areas are in isolated areas and those that are not isolated.